Economically viable aquaponics? Identifying the gap between potential and current uncertainties - Greenfeld, A.; Becker, N.; Mcilwain, J.; Fotedar, Ravi; Bornman, J. (2018)
Aquaponics, which integrates hydroponic farming and aquaculture, has the potential for sustainably producing high-quality food, but has yet to achieve commercial success. In recent years, however, commercial-scale aquaponics has received considerable attention from the scientific community, with the current literature covering many aspects of aquaponic production. We reviewed this literature and classified the specific areas covered by each paper and its contribution to either cost reduction or benefit enhancement. The literature regarding the economic benefits of aquaponics was summarised, and despite contradicting views of current profitability, there is a consensus that (i) larger systems are economically superior to smaller ones; (ii) profitability is sensitive to retail prices; and (iii) commercial aquaponics are more profitable through improved business plans. This review provides a quantitative scientific analysis of the bioeconomics and potential of commercial aquaponics, useful for both researchers and practitioners. We argue for greater focus on three understudied aspects that could each be a 'game changer' for commercial aquaponics. These include the following: (i) grower considerations such as financial planning and risk management that affect potential growers' initial engagement in aquaponics; (ii) consumer perception of aquaponic products including the willingness to pay more for its added value; and (iii) the economic value of the environmental benefits of aquaponic systems and ways to internalise them for profit. Further study of each of these aspects, along with the ongoing improvement of production systems, will support the establishment of large-scale aquaponics as an economically sustainable industry.